Monte Carlo Ray-Tracing Simulation of a Cassegrain Solar Concentrator Module for CPV - Oh, Seung Jin; Kim, Hyungchan; Hong, Youngsun (Frontiers in Energy Research, 2021)
The concentration ratio is one of the most important characteristics in designing a Cassegrain solar concentrator since it directly affects the performance of high-density solar energy applications such as concentrated photovoltaics (CPVs). In this study, solar concentrator modules that have different configurations were proposed and their performances were compared by means of a Monte Carlo ray-tracing algorithm to identify the optimal configurations. The first solar concentrator design includes a primary parabolic concentrator, a parabolic secondary reflector, and a homogenizer. The second design, on the other hand, includes a parabolic primary concentrator, a secondary hyperbolic concentrator, and a homogenizer. Two different reflectance were applied to find the ideal concentration ratio and the actual concentration ratio. In addition, uniform rays and solar rays also were compared to estimate their efficiency. Results revealed that both modules show identical concentration ratios of 610 when the tracking error is not considered. However, the concentration ratio of the first design rapidly drops when the sun tracking error overshoots even 0.1°, whereas the concentration ratio of the second design remained constant within the range of the 0.8° tracking error. It was concluded that a paraboloidal reflector is not appropriate for the second mirror in a Cassegrain concentrator due to its low acceptance angle. The maximum collection efficiency was achieved when the f-number is smaller and the rim angle is bigger and when the secondary reflector is in a hyperboloid shape. The target area has to be rather bigger with a shorter focal length for the secondary reflector to obtain a wider acceptance angle.